Biology - Ismael, Deborah [UNESP]; New, Michael Bernard (Wiley, 2007)
Most of the information in this chapter is concerned with Macrobrachium rosenbergii. However, where specific information is lacking, other closely related crustaceans are used for illustrative purposes, it being reasonable to assume that their biology does not differ substantially. This chapter is not intended to be a complete treatise on decapod biology, merely a summary of those facets of Macrobrachium biology that are relevant to its aquaculture. For a more detailed account of decapod biology a most elegant recent publication about the American lobster (Factor 1995) may be consulted.
Keywords: Habitat of macrobrachium rosenbergii; Life cycle; Mating; Morphology; Tropical freshwater